PHARMACOGNOSTIC AND PHARMACOLOGICAL ACTIVITY OF EULOPHIA NUDA LIND- A REVIEW - VAISHALI NAGULWAR; MADHURI NANDGAVE (International Journal of Pharma and Bio Sciences, 2016)
The plants belonging to family Orchidaceae are known to have various medicinal values. They are considered to be a herbal aphrodisiac and to have therapeutic values, ranging from preventing headaches to counteracting poisons and bites. It is all the more difficult to confirm the identity of the plant. It shows their macroscopic, microscopic characters. The more amounts of Phytoconstituents is present like steroids, alkaloids, flavonoids, saponins etc. The gastro protective effect of ETHAB may be attributed to antioxidant activity, increased gastric wall mucus, pH level of gastric contents, SOD activity, and decrease in MDA level, ulcer area, flattening of gastric mucosa, and reduction of edema and leucocyte infiltration of the sub mucosal layer. Lower concentrations of plant extract produced either no or least response against advanced glycation end products (AGEs). The DNA from hydroxyl radical-induced damage. Again, AqME was proved to be best in providing protection to DNA against damage caused by free radicals